The Influence of Brand Equity to Purchasing Decisions on Wardah Products (studies conducted at Wardah Beauty House stores, Surabaya) - Vebri Aria Rahma (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2018)
This study aims to analyze the influence of brand equity which includes: brand awareness, brand association, perceived quality, and brand loyalty on purchasing decisions at Wardah Beauty House Surabaya stores. The authors used a survey, where the authors distributed questionnaires totaling 100 questionnaires to consumers or customers in Wardah Beauty House Surabaya stores. This is a quantitative research. Analyzed using multiple linear regression analisys and using SPSS 18.0. Based on the results of the study showed that brand equity variables consisting of brand awareness, brand association, perceived quality, and brand loyalty simultaneously have a significant effect on purchasing decisions. Brand awareness doesn’t have a partially significance influence on purchasing decisions.